Kekuasaan seksualitas dalam cerpen Eka Kurniawan: Analisis Wacana Michel Foucault - Permana, Sugihartini (Jurnal Lazuardi, 2024)
This research aims to analyze the discourse of sexual power in a short story entitled Interpreter of Happiness. This research takes the form of qualitative descriptive. The object of this research is one of Eka Kurniawan's short stories in Eka Kurniawan's short story anthology book entitled "Woman with a Broken Heart Finding love through dreams.” This research uses an approach Michel Foucault's genealogy of power perspective which aims to dissect the relationships and influences that arise from the relations of each discourse of power sexuality in the short story Interpreter of Happiness.